Insulin-Degrading Enzyme Regulates the Proliferation and Apoptosis of Porcine Skeletal Muscle Stem Cells via Myostatin/MYOD Pathway - Wang, Bingyuan; Guo, Jiankang; Zhang, Mingrui; Liu, Zhiguo; Zhou, Rong; Guo, Fei; Li, Kui; Mu, Yulian (Frontiers in Cell and Developmental Biology, 2021)
Identifying the genes relevant for muscle development is pivotal to improve meat production and quality in pigs. Insulin-degrading enzyme (IDE), a thiol zinc-metalloendopeptidase, has been known to regulate the myogenic process of mouse and rat myoblast cell lines, while its myogenic role in pigs remained elusive. Therefore, the current study aimed to identify the effects of IDE on the proliferation and apoptosis of porcine skeletal muscle stem cells and underlying molecular mechanism. We found that IDE was widely expressed in porcine tissues, including kidney, lung, spleen, liver, heart, and skeletal muscle. Then, to explore the effects of IDE on the proliferation and apoptosis of porcine skeletal muscle stem cells, we subjected the cells to siRNA-mediated knockdown of IDE expression, which resulted in promoted cell proliferation and reduced apoptosis. As one of key transcription factors in myogenesis, MYOD, its expression was also decreased with IDE knockdown. To further elucidate the underlying molecular mechanism, RNA sequencing was performed. Among transcripts perturbed by the IDE knockdown after, a down-regulated gene myostatin (MSTN) which is known as a negative regulator for muscle growth attracted our interest. Indeed, MSTN knockdown led to similar results as those of the IDE knockdown, with upregulation of cell cycle-related genes, downregulation of MYOD as well as apoptosis-related genes, and enhanced cell proliferation. Taken together, our findings suggest that IDE regulates the proliferation and apoptosis of porcine skeletal muscle stem cells through MSTN/MYOD pathway. Thus, we recruit IDE to the gene family of regulators for porcine skeletal muscle development, and propose IDE as an example of gene to prioritize in order to improve pork production.